A practical optical and electrical model to estimate the power losses and quantification of different heat sources in silicon based PV modules. (November 2018) - Hanifi, Hamed; Pfau, Charlotte; Turek, Marko; Schneider, Jens
Abstract: Solar modules convert light in wanted electricity, unwanted heat and reflected incident light. Light absorbed in the silicon of the solar cells generates free charge carriers which are converted into electricity by the photovoltaic effect. Some of the energy absorbed in free charge carriers as well as all other absorption in non-photoactive layers generates heat. PV modules are mainly characterized in standard test conditions (STC) but quantification of reflection losses and heat sources in PV modules helps to evaluate the yield of PV modules in different spectrums and environmental conditions such as desert regions where the module temperature can influence the energy yield. In this work, we introduce a practical method for calculating spectrally resolved absorption and voltage resolved electrical conversion mechanisms in order to quantify electricity and heat generating processes by means of common characterization devices. The model only needs optical characterization of module components and typical electrical characterization of the cells and modules. Based on the performance of individual components, the share of each loss phenomena and electricity production in the complete solar module can be determined. Comparison of simulation results with experimental measurements shows a good correlation. The measured and simulated short-circuit current density are in good agreement with about 1% deviation due to additional back reflections and measurement noise. The cell to module (CTM) current loss are simulated and measured for 2.63% and 1.85% respectively. The results show that for the measured modules, 7% of the incoming solar power on the module is reflected while 75.58% of it turns to heat. The usable energy as electricity is simulated and measured for 17.44% and 17.72%, respectively. We show that more than half of the incoming energy dissipates as heat due to thermalization and thermodynamic losses. Graphical abstract: Image 1 Highlights: A Spectrally dependent optical and voltage dependent electrical model for PV modules. Quantification of heat sources, optical reflections and electricity in module level. About 7% of the light on module level is being reflected while 75.58% turns to heat. The measured and simulated short-circuit current density are in good accordance. The average efficiency is measured for 17.72% and simulated for 17.44%.